High-thermal-conductivity adhesive film of phase change material as well as preparation method and application of high-thermal-conductivity adhesive film
By combining polyethylene glycol-modified acrylate resin with polyethylene glycol phase change material and thermally conductive filler, a high thermal conductivity adhesive film was prepared, which solved the compatibility problem between the phase change material and the adhesive film and achieved good bonding stability and thermal conductivity.
Patent Information
- Application Number
- CN202511419581.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2025-12-02
AI Technical Summary
Existing phase change materials have poor compatibility with adhesive films, affecting adhesion and bonding stability. Furthermore, the chemical bonding process is difficult to control and may reduce bonding performance.
A high thermal conductivity adhesive film was prepared by using polyethylene glycol modified acrylate resin as the base adhesive component, which forms good physical compatibility with polyethylene glycol phase change material, and combined with thermally conductive fillers.
It significantly improves the bonding stability and thermal conductivity of the adhesive film. The polyethylene glycol phase change material does not precipitate during the phase change process and maintains good adhesion.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adhesive materials technology, specifically relating to a high thermal conductivity adhesive film of phase change material, its preparation method and application. Background Technology
[0002] In 3C electronic products and new energy vehicle power batteries, adhesive films are commonly used to bond and fix electronic components, circuits and circuit boards, electromagnetic shielding materials, and thermally conductive materials. This method offers advantages such as ease of use, simple structure, and lightweight design. However, these devices generate significant amounts of heat during operation. Accumulated heat can lead to thermal runaway, posing safety risks. Furthermore, increased temperature reduces the adhesive strength of the adhesive film, resulting in decreased device stability.
[0003] Phase change materials (PCMs) are a class of substances capable of absorbing or releasing a large amount of latent heat through physical phase transitions (such as solid-liquid and liquid-gas transitions) within a specific temperature range. Taking solid-liquid phase transition as an example, when the temperature rises to the melting temperature, a phase transition occurs from solid to liquid. During melting, the PCM absorbs and stores a large amount of latent heat. When the temperature decreases, a reverse phase transition occurs from liquid to solid, and the stored heat is dissipated into the environment. During both phase transitions, the material temperature remains essentially stable. Therefore, applying PCMs to adhesive films can, to a certain extent, absorb heat generated by the device and maintain a stable device temperature.
[0004] Commonly used phase change materials (PCMs) include polyethylene glycol (PEG) and paraffin wax, but these PCMs generally have poor compatibility with adhesive films, affecting adhesion and bonding stability. Therefore, the main technical challenge in applying PCMs to adhesive films lies in solving the compatibility problem. Patent CN 112409942 A describes a heat-dissipating encapsulating film, which includes a matrix resin and a PCM / thermal conductive filler composite dispersed in the matrix resin, an initiator, and a crosslinking agent. The PCM / thermal conductive filler composite is a composite formed by chemically bonding the PCM and the thermal conductive filler through a first silane coupling agent. However, chemically bonding the PCM and the thermal conductive filler carries the risk of altering the phase change properties of the PCM, and the significant difference in reactivity between the PCM and the thermal conductive filler makes process control for chemical bonding difficult. Furthermore, the thermal conductive filler chemically bonded to the PCM reduces the compatibility between the filler and the adhesive film, thus reducing the adhesive film's bonding performance. Summary of the Invention
[0005] In view of the shortcomings and deficiencies of the existing technology, the primary objective of this invention is to provide a high thermal conductivity adhesive film for phase change materials.
[0006] Another object of the present invention is to provide a method for preparing a high thermal conductivity adhesive film of the above-mentioned phase change material.
[0007] Another object of the present invention is to provide the application of the high thermal conductivity adhesive film of the above-mentioned phase change material in 3C electronic products and power battery devices for new energy vehicles.
[0008] The objective of this invention is achieved through the following technical solution: A high thermal conductivity adhesive film for a phase change material comprises a release film, an adhesive film, and a protective film arranged sequentially. The adhesive film has the following composition by mass percentage: Polyethylene glycol modified acrylate resin 45-85%; Thermally conductive filler 10-30%; Polyethylene glycol phase change materials 5-25%; The polyethylene glycol modified acrylate resin is obtained by polymerizing acrylate monomers, acrylonitrile, and polyethylene glycol acrylate monomers.
[0009] Further, the acrylate monomer is at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, isooctyl methacrylate, and glycidyl methacrylate.
[0010] Furthermore, the polyethylene glycol acrylate monomer is polyethylene glycol methacrylate (CH2=C(CH3)CO(OCH2CH2) with a molecular weight of 1000-4000. n OH) or polyethylene glycol acrylate (CH2=CHCO(OCH2CH2) n OH).
[0011] Furthermore, the molar ratio of the acrylate monomer, acrylonitrile, and polyethylene glycol acrylate monomer polymerized is 10:3-6:1-2.
[0012] Furthermore, the thermally conductive filler is at least one of alumina, aluminum nitride, boron nitride, and silicon carbide.
[0013] Furthermore, the polyethylene glycol phase change material is polyethylene glycol with a molecular weight of 1000-10000.
[0014] Furthermore, the protective film is a PE (polyethylene) protective film or a PET (polyethylene terephthalate) protective film.
[0015] The preparation method of the high thermal conductivity adhesive film of the above-mentioned phase change material includes the following preparation steps: (1) Add acrylate monomer, acrylonitrile and polyethylene glycol acrylate monomer to an organic solvent, add an initiator under nitrogen protection and heat to polymerize, to obtain a polyethylene glycol modified acrylate resin solution; (2) Add the thermally conductive filler and polyethylene glycol phase change material to the polyethylene glycol modified acrylate resin solution obtained in step (1) and mix well. Then coat the mixed adhesive solution onto the protective film and dry and cure it to obtain an adhesive film. Finally, cover the adhesive film with a release film to obtain a high thermal conductivity adhesive film of phase change material.
[0016] Preferably, the organic solvent in step (1) is at least one of benzene, toluene, ethyl acetate, acetone, tetrahydrofuran, cyclohexane, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0017] Preferably, the initiator in step (1) is benzoyl peroxide or azobisisobutyronitrile; the temperature of the heating polymerization reaction is 60~80℃ and the time is 3~6h.
[0018] The application of the high thermal conductivity adhesive film of the above phase change material in 3C electronic products and power battery devices for new energy vehicles.
[0019] Compared with the prior art, the beneficial effects of the present invention are: (1) The adhesive film of the present invention uses polyethylene glycol modified acrylate resin as the base adhesive component, which has good physical compatibility with polyethylene glycol phase change material, thereby significantly reducing the influence of polyethylene glycol phase change material on the adhesive performance, and without affecting the phase change performance of polyethylene glycol phase change material.
[0020] (2) The present invention uses polyethylene glycol modified acrylate resin as the main adhesive, which can significantly reduce the precipitation of polyethylene glycol from the adhesive film during the phase change process and improve the bonding stability. Detailed Implementation
[0021] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto. Example 1
[0022] A method for preparing a high thermal conductivity adhesive film of a phase change material includes the following preparation steps: (1) Butyl acrylate, acrylonitrile and polyethylene glycol acrylate with an average molecular weight of 2000 were added to toluene solvent in a molar ratio of 10:4.5:1.5. Benzoyl peroxide initiator was added under nitrogen protection and the mixture was heated to 70~75℃ for 4h to obtain polyethylene glycol modified acrylate resin solution.
[0023] (2) Add the thermally conductive filler aluminum nitride and polyethylene glycol phase change material PEG-2000 to the polyethylene glycol modified acrylate resin solution obtained in step (1) and mix well. The mass percentage of each component is: polyethylene glycol modified acrylate resin 65%, aluminum nitride 20%, PEG-2000 15%. Then coat the mixed adhesive solution onto a PET protective film and dry and cure it to obtain an adhesive film. Finally, cover the adhesive film with a release film to obtain a high thermal conductivity adhesive film of phase change material.
[0024] The high thermal conductivity adhesive film of the phase change material obtained in this embodiment has a tested thermal conductivity of 1.36 W / m·K; its initial peel strength (GB / T 2792-2014) is 5.3 N / 25 mm; and its peel strength after 10 phase change reactions (heating the adhesive film in a constant temperature oven to above the melting point of PEG-2000 for 10 min, then cooling to room temperature and allowing it to stand for 10 min) is 4.7 N / 25 mm. This indicates that the high thermal conductivity adhesive film of the phase change material obtained in this invention has good thermal conductivity, adhesion, and bonding stability. Example 2
[0025] A method for preparing a high thermal conductivity adhesive film of a phase change material includes the following preparation steps: (1) Ethyl acrylate, acrylonitrile and polyethylene glycol acrylate with an average molecular weight of 3000 were added to toluene solvent in a molar ratio of 10:6:2. Benzoyl peroxide initiator was added under nitrogen protection and the mixture was heated to 70~75℃ for 4h to obtain polyethylene glycol modified acrylate resin solution.
[0026] (2) Add the thermally conductive filler alumina and polyethylene glycol phase change material PEG-4000 to the polyethylene glycol modified acrylate resin solution obtained in step (1) and mix well. The mass percentage of each component is: polyethylene glycol modified acrylate resin 65%, alumina 30%, and PEG-4000 5%. Then coat the mixed adhesive solution onto a PET protective film and dry and cure it to obtain an adhesive film. Finally, cover the adhesive film with a release film to obtain a high thermal conductivity adhesive film of phase change material.
[0027] The high thermal conductivity adhesive film of the phase change material obtained in this embodiment has a tested thermal conductivity of 1.40 W / m·K; its initial peel strength (GB / T 2792-2014) is 5.6 N / 25 mm; and its peel strength after 10 phase change reactions (heating the adhesive film in a constant temperature oven to above the melting point of PEG-4000 and maintaining it for 10 min, then cooling it to room temperature and allowing it to stand for 10 min) is 5.2 N / 25 mm. This indicates that the high thermal conductivity adhesive film of the phase change material obtained in this invention has good thermal conductivity, adhesion, and bonding stability. Example 3
[0028] A method for preparing a high thermal conductivity adhesive film of a phase change material includes the following preparation steps: (1) Butyl acrylate, acrylonitrile and polyethylene glycol methacrylate with an average molecular weight of 1000 were added to toluene solvent in a molar ratio of 10:3:1. Under nitrogen protection, azobisisobutyronitrile initiator was added and the mixture was heated to 65~70℃ for 4h to obtain polyethylene glycol modified acrylate resin solution.
[0029] (2) Add the thermally conductive filler boron nitride and polyethylene glycol phase change material PEG-1000 to the polyethylene glycol modified acrylate resin solution obtained in step (1) and mix well. The mass percentage of each component is: polyethylene glycol modified acrylate resin 65%, boron nitride 10%, PEG-1000 25%. Then coat the mixed adhesive solution onto a PET protective film and dry and cure it to obtain an adhesive film. Finally, cover the adhesive film with a release film to obtain a high thermal conductivity adhesive film of phase change material.
[0030] The high thermal conductivity adhesive film of the phase change material obtained in this embodiment has a tested thermal conductivity of 1.21 W / m·K; its initial peel strength (GB / T 2792-2014) is 4.9 N / 25 mm; and its peel strength after 10 phase change reactions (heating the adhesive film in a constant temperature oven to above the melting point of PEG-1000 and maintaining it for 10 min, then cooling it to room temperature and allowing it to stand for 10 min) is 4.1 N / 25 mm. This indicates that the high thermal conductivity adhesive film of the phase change material obtained in this invention has good thermal conductivity, adhesion, and bonding stability. Example 4
[0031] A method for preparing a high thermal conductivity adhesive film of a phase change material includes the following preparation steps: (1) Isooctyl acrylate, acrylonitrile and polyethylene glycol acrylate with an average molecular weight of 4000 were added to benzene solvent in a molar ratio of 10:4:2. Under nitrogen protection, azobisisobutyronitrile initiator was added and the mixture was heated to 65~70℃ for 4h to obtain polyethylene glycol modified acrylate resin solution.
[0032] (2) Add the thermally conductive filler silicon carbide and polyethylene glycol phase change material PEG-6000 to the polyethylene glycol modified acrylate resin solution obtained in step (1) and mix well. The mass percentage of each component is: polyethylene glycol modified acrylate resin 65%, silicon carbide 15%, PEG-6000 20%. Then coat the mixed adhesive solution onto a PE protective film and dry and cure it to obtain an adhesive film. Finally, cover the adhesive film with a release film to obtain a high thermal conductivity adhesive film of phase change material.
[0033] The high thermal conductivity adhesive film of the phase change material obtained in this embodiment has a tested thermal conductivity of 1.32 W / m·K; its initial peel strength (GB / T 2792-2014) is 5.2 N / 25 mm; and its peel strength after 10 phase change reactions (heating the adhesive film in a constant temperature oven to above the melting point of PEG-6000 for 10 min, then cooling to room temperature and allowing it to stand for 10 min) is 4.5 N / 25 mm. This indicates that the high thermal conductivity adhesive film of the phase change material obtained in this invention has good thermal conductivity, adhesion, and bonding stability.
[0034] Comparative Example 1 A method for preparing a high thermal conductivity adhesive film of a phase change material includes the following preparation steps: (1) Add butyl acrylate and acrylonitrile in a molar ratio of 10:4.5 to toluene solvent, add benzoyl peroxide initiator under nitrogen protection, and heat to 70~75℃ for 4h to polymerize and obtain acrylate resin solution.
[0035] (2) Add the thermally conductive filler aluminum nitride and polyethylene glycol phase change material PEG-2000 to the acrylate resin solution obtained in step (1) and mix well. The mass percentage of each component is: acrylate resin 65%, aluminum nitride 20%, PEG-2000 15%. Then coat the mixed adhesive solution onto a PET protective film and dry and cure it to obtain an adhesive film. Finally, cover the adhesive film with a release film to obtain a high thermal conductivity adhesive film of phase change material.
[0036] The high thermal conductivity adhesive film of the phase change material obtained in this comparative example has a tested thermal conductivity of 1.33 W / m·K; an initial peel strength (GB / T 2792-2014) of 4.0 N / 25 mm; and a peel strength of 2.9 N / 25 mm after 10 phase change reactions (heating the adhesive film in a constant temperature oven to above the melting point of PEG-2000 for 10 min, and then cooling it to room temperature and letting it stand for 10 min).
[0037] The comparison between the results of this comparative example and Example 1 shows that the present invention uses polyethylene glycol modified acrylate resin as the main adhesive and combines it with polyethylene glycol phase change material, which can significantly improve the adhesion and bonding stability of the adhesive film.
[0038] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A high thermal conductivity adhesive film for phase change material, comprising a release film, an adhesive film, and a protective film arranged sequentially, characterized in that: The adhesive film has the following composition by weight percentage: Polyethylene glycol modified acrylate resin 45-85%; Thermally conductive filler 10-30%; Polyethylene glycol phase change material 5-25%; The polyethylene glycol modified acrylate resin is obtained by polymerizing acrylate monomers, acrylonitrile, and polyethylene glycol acrylate monomers.
2. The high thermal conductivity adhesive film of phase change material according to claim 1, characterized in that: The acrylate monomer is at least one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, isooctyl methacrylate, and glycidyl methacrylate.
3. The high thermal conductivity adhesive film of phase change material according to claim 1, characterized in that: The polyethylene glycol acrylate monomer is polyethylene glycol methacrylate or polyethylene glycol acrylate with a molecular weight of 1000-4000.
4. The high thermal conductivity adhesive film of phase change material according to claim 1, characterized in that: The molar ratio of the acrylate monomer, acrylonitrile, and polyethylene glycol acrylate monomer polymerized is 10:3-6:1-2.
5. The high thermal conductivity adhesive film of phase change material according to claim 1, characterized in that: The thermally conductive filler is at least one of alumina, aluminum nitride, boron nitride, and silicon carbide.
6. The high thermal conductivity adhesive film of phase change material according to claim 1, characterized in that: The polyethylene glycol phase change material is polyethylene glycol with a molecular weight of 1000-10000.
7. The high thermal conductivity adhesive film of phase change material according to claim 1, characterized in that: The protective film is a PE protective film or a PET protective film.
8. A method for preparing a high thermal conductivity adhesive film of a phase change material according to any one of claims 1-7, characterized in that: The preparation steps include the following: (1) Add acrylate monomer, acrylonitrile and polyethylene glycol acrylate monomer to an organic solvent, add an initiator under nitrogen protection and heat to polymerize, to obtain a polyethylene glycol modified acrylate resin solution; (2) Add the thermally conductive filler and polyethylene glycol phase change material to the polyethylene glycol modified acrylate resin solution obtained in step (1) and mix well. Then coat the mixed adhesive solution onto the protective film and dry and cure it to obtain an adhesive film. Finally, cover the adhesive film with a release film to obtain a high thermal conductivity adhesive film of phase change material.
9. The method for preparing a high thermal conductivity adhesive film of a phase change material according to claim 8, characterized in that: The organic solvent in step (1) is at least one of benzene, toluene, ethyl acetate, acetone, tetrahydrofuran, cyclohexane, N,N-dimethylformamide, and N,N-dimethylacetamide; the initiator is benzoyl peroxide or azobisisobutyronitrile; the temperature of the heating polymerization reaction is 60~80℃ and the time is 3~6h.
10. The application of a high thermal conductivity adhesive film of phase change material according to any one of claims 1-7 in 3C electronic products and power battery devices for new energy vehicles.
Citation Information
Patent Citations
Heat dissipation type packaging adhesive film and preparation method thereof
CN112409942A